1997
DOI: 10.1111/j.1744-6570.1997.tb00911.x
|View full text |Cite
|
Sign up to set email alerts
|

A Meta‐analysis of the Relations Among Training Criteria

Abstract: An augmented framework for training criteria based on Kirkpatrick's (1959a, 1959b, 1960a, 1960b) model divides training reactions into affective and utility reactions, and learning into post‐training measures of learning, retention, and behavior/skill demonstration. A total of 34 studies yielding 115 correlations were analyzed meta‐analytically. Results included substantial reliabilities across training criteria and reasonable convergence among subdivisions of criteria within a larger level. Utility‐type react… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

45
557
8
41

Year Published

2000
2000
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 712 publications
(683 citation statements)
references
References 51 publications
45
557
8
41
Order By: Relevance
“…The literature has shown links between the constructs of training transfer and training effectiveness (Alliger, Tannenbaum, Bennett, Traver, & Shotland, 1997;Cannon-Bowers et al, 1995;Salas et al, 2003). The more common connection has been to use training transfer in combination with other constructs such as pretraining motivation and other factors such as tests scores from evaluations given at the training, and evaluations scores from on the job, to form training effectiveness (Baldwin & Ford, 1988).…”
Section: Connections Between Training Transfer and Training Effectivementioning
confidence: 99%
“…The literature has shown links between the constructs of training transfer and training effectiveness (Alliger, Tannenbaum, Bennett, Traver, & Shotland, 1997;Cannon-Bowers et al, 1995;Salas et al, 2003). The more common connection has been to use training transfer in combination with other constructs such as pretraining motivation and other factors such as tests scores from evaluations given at the training, and evaluations scores from on the job, to form training effectiveness (Baldwin & Ford, 1988).…”
Section: Connections Between Training Transfer and Training Effectivementioning
confidence: 99%
“…Level 1 evaluations may assess affective reactions, such as level of satisfaction and enjoyment of the training, and utility judgments, such as perceived relevance and practical value of the training for subsequent job performance. 8 To measure reactions to training provided by the SCCPHP, the Teaching and Learning Environment Questionnaire-Distance Learning Form (TLEQ-D) was developed to assess trainee reactions. 9 In accordance with recommended guidelines for survey development, 10 the questionnaire was validated by standardized procedures to ensure that responses reflect appropriate opinions of the training participants (i.e., reviewed by subject matter experts including representatives of the health departments for clarity and completeness).…”
Section: Level 1: Reactionsmentioning
confidence: 99%
“…10 Although the Level 1 evaluations do not directly measure student learning, research in adult learning and training has demonstrated that utility-type reactions, also measured by the TLEQ-D, are significantly correlated with knowledge acquisition and performance of the training on the job and can serve as useful indicators of student learning and performance. 8,11 Level 2: Learning Level 2 evaluations are designed to measure the extent to which the students acquired the principles, facts, techniques, and attitudes stated in the learning objectives. Multiple choice and essay examinations, case studies, behavioral role plays, and scenario-based simulated exercises are examples of Level 2 tools used to assess student learning.…”
Section: Level 1: Reactionsmentioning
confidence: 99%
“…In other words, the ownership concentration, firm's size, and board structure play important roles in determining the success of the TDP, which is in line with the alignment theorem. Moreover, most of the research conducted in this area only evaluates TDP using reaction criteria (Alliger et al 1997;Kraiger 2003;Kraiger et al 2004), and surveys (Nguyen et al 2011;Ganotakis 2012). Hence this research aims to bridge the research gap in this area.…”
Section: Introductionmentioning
confidence: 99%